The Role of Interleukin-1 Genotype in the Association between Coronary Heart Disease and Periodontitis in a Syrian Population. (14th April 2013) - Bashour, Lina; Khattab, Razan; Harfoush, Elham
Abstract : Objective . To determine whether differences exist between periodontitis subjects with and without Coronary Heart Disease (CHD) in a Syrian population in the distribution of IL-1 alleles at positions IL-1α +4845, IL-1β +3954, IL-1β −511, and IL-1RN VNTR. Background . The role of Interleukin-1 genes in the association between periodontitis and CHD has been demonstrated in previous studies. No study has been carried out on the Syrian population to asses for such a role. Methods . 200 Syrian Arab periodontitis patients (184 males, 16 females; mean age 52.61) were divided into two groups: cases group 100 subjects with CHD (92 males, 8 females; mean age 52.06); controls group 100 subjects without CHD (92 males, 8 females; mean age 53.16). Probing depth (PD), clinical attachment loss (CAL), and alveolar bone loss (ABL) were performed for patients. Blood samples were collected for genotyping analysis of IL-1α +4845, IL-1β +3954, and IL-1β −511 using PCR-RFLP technique and IL-1RN VNTR using normal PCR. Results . An association between both (CAL and ABL) and CHD was shown after adjustment for other confounders (OR: 7.659, P = 0 . 00 1 ; OR: 3.645, P = 0 . 00 6, resp.). Also, an association between allele 2 of IL-1α +4845, IL-1β +3954, and IL-1β −511 and ABL was shown. Allele 2 of IL-1α +4845 and IL-1β −511 was associated with ABL among individuals with and without CHD. But after adjustment for other confounders, the association remained only between allele 2 of IL-11α +4845 and both CHD and severe ABL (OR: 0.189, P < 0.001 ). Conclusion . Allele 2 of IL-11α +4845 may be considered a risk indicator for having both CHD and severe ABL in the investigated Syrian population.